ChemInform Abstract: Diastereoselective Syntheses of Highly Substituted Methylenecyclopropanes via Copper‐ or Iron‐Catalyzed Reactions of 1, 2‐Disubstituted 3‐(Hydroxymethyl)cyclopropenes with Grignard Reagents. Issue 43 (7th October 2013) - Xie, Xiaocong; Fox, Joseph M.
Abstract The Cu(I)‐catalyzed reaction of substituted cyclopropenes with Grignard reagents proceeds with good to high diastereoselectivity providing the syn‐addition products (III).